Alocação diferencial do 13C em Copaifera langsdorffii Desf. (Fabaceae - Caesalpinoideae) sob deficiência hídrica - Bertholdi, Angelo Albano da Silva [UNESP] (2015)
Drought is one of the most factors that influence the growth and the productivity of plants. The biochemical and molecular responses during water stress are essential to activate mechanisms of plant resistance. Many tree species have morphological, physiological and biochemical mechanisms to overcome damage caused by water stress. Such changes are modidications on the pattern of growth, development of vegetative organs, changes in stomatal conductance, osmotic potential adjustment of tissues and production of substances from secondary metabolism. All these changes may cause modifications on the isotopic 13C/12C ratio in different vegetative organs of the plant, as well as in organic compounds produced and stored on tissues. We evaluated the water relations and photochemical efficiency in Copaifera langsdorffii Desf. under different water conditions and related it with the changes on the organic and natural relative enrichment 13C/12C. The water relations characteristics decreased at the end of the period of water deficit and water recover at the end of the rehydration period. The analyzes regarding the photochemical steps showed significant changes at the end of the rehydration period. The high values of electron transport rate and photochemical quenching may have aided in the recovery of damages caused by photoinhibition during water deficit period. The resumption of photochemical activity after rehydration pointed photoprotection capacity of C. langsdorffi in water deficit conditions. The end of the drought period did not show differences in natural isotopic ratio 13C / 12C, and the leaves and residue of essential oil extraction was 13C enrichment in essential oil, and lipids extracted from the leaves observed depletion in 13C. Furthermore, in drought period, leaves and principal root decreased the amount of starch and soluble sugars